Efek Pendapatan Keluarga Terhadap Jumlah Karies Gigi Pada Anak Sekolah Dasar - Eni Purwati, Dwi; Almujadi, Almujadi; Suyatmi, Dwi (Poltekkes Kemenkes Yogyakarta, 2018)
Healthy life behavior can be influenced by someone's social economy. One of the factors that influence it is income or income. Earnings have a direct influence on medical care, if income increases, then the cost of health also increases. Medical treatment is one of them is a cavity in the cavities (dental caries). Dental caries is more common in children's school. The results of 8 children shcool on average have caries 2 in Muhammadiyah Sambisari Kalasan Elementary School. The purpose of research: To knowing about the influence of parental income on child dental caries in Muhammadiyah Sambisari Elementary School. Research design: cross sectional, type of research: analytic, data collection technique: observational and survey, sample: 60 children (random sampling) at 3, 4, 5 grade, Data analysis: Wilcoxon test. The result of the analysis using wilcoxon test influence the amount of income per month of parent, to the amount of dental caries student is the value of Asymp. The Sig is 0.012 is less than 0.05 so, Ho can be reject and Ha will be accept, then statistically shows a significant influence between income level per month of parent to number of dental caries of Sambisari elementary school.